A semiconductor strain gage tactile transducer - Obana, F. Y.; Carvalho, A. A.; Gualda, R.; da Silva, J. G. (Institute of Electrical and Electronics Engineers (IEEE), 2001)
This paper describes the development of a semiconductor strain gage tactile transducer. It was designed with the goal of measuring finger forces without affecting the hand dexterity. The transducer structure was manufactured with stainless steel and has small dimensions ( 4 min diameter and I min thickness). It is light and suitable to connect to the finger pads. It has a device that prevents its damage when forces are applied. The semiconductor strain gage was used over due its small size and high sensitivity, although it has high temperature sensitivity. Theory, design and construction details are presented the signal conditioning circuit is very simple because the semiconductor strain gage sensitivity is high. It presents linear response from 0 to 100 N, 0.5 N resolution, fall time of 7.2 ms, good repeatability, and small hysteresis. The semiconductor strain gage transducer has characteristics that can make it very useful in Rehabilitation Engineering, Robotics, and Medicine.
Keywords: semiconductor strain gage; tactile transducer; force sensor; finger force; semiconductor sensor